Phycoremediation potential of Chlorella sp. on the polluted Thirumanimutharu river water - Narayanan, Mathiyazhagan (2021)
Rivers are the most significant natural resources that afford outstanding habitation and nourishment for numerous living organisms. Urbanization and industrialization pollute rivers rendering their water unhealthy for consumption. Hence, this work was designed to find a potential native pollutant removing algae from polluted water. The physicochemical properties of the tested river water such as Electric Conductivity (EC), turbidity, total hardness, Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Ca, SO2-, and NH3, NO3, NO2, PO4, Mg, F- and Cl- contents were not within the permissible limits. Lab-scale and field-based phycoremediation treatments with the indigenous native microalgal species, Chlorella sp. from the Thirumanimutharu river water sample were set up for 15 days with three different (Group I, II, and III) biomass densities (4 × 104, 8 × 104, and 12 × 104 cells mL-1). Group III of both the lab-scale and field based treatments showed the maximum reduction in the physicochemical parameters compared to the other groups. Further, the group III of the field based study showed an extensive reduction in BOD (34.51%), COD (32.53%), NO3, NO2, free NH3 (100%) and increased dissolved oxygen (DO) (88.47%) compared to the lab scale study. In addition, the trace elements were also reduced significantly. The pollutant absorbing active functional moieties (O-H, CO, and CN) found on Chlorella sp. had been confirmed by Fourier-Transform Infrared Spectroscopy (FTIR) analysis. In the Scanning Electron Microscope (SEM) study, significant morphological changes on the surface of the treated Chlorella sp. were noticed compared with the untreated Chlorella sp. biomass, which also confirmed the absorption of the pollutants during treatment.